PENGURAIAN TANDA (DECODING) PADA RUMOH ACEH DENGAN PENDEKATAN SEMIOTIKA (Elaboration of Sign (Decoding) of Rumoh Aceh Using Semiotics Approach) - Riza Aulia Putra; Agus Suharjono Ekomadyo (Universitas Katolik Soegijapranata, 2015)
Rumoh Aceh is one of the artefacts from the cultural society. As a cultural artefact, rumoh Aceh can be read as a text that represented of a society tradition. There are messages that are contained in rumoh Aceh. The architecture of rumoh Aceh has been influenced by Islam as a majority religion in the society. To be able to know the message that attach in the architecture of rumoh Aceh, it is needed to elaborate the architectural components. Semiotics is one of method that can be used to read or disclose the message that contain in architectural object based on an existing signature or code (decoding). The process of elaboration of the sign using semiotic approach relies heavily on social agreements in a society where the object of architecture is located. The purpose of this article is to expose the messages attach in the architecture of rumohAceh as an efforts of transposition in order to appreciate and preserve the values of architecture of rumoh Aceh so that it can eventually be translated into new architectural forms in the present context.